EXPLORING THE EVOLUTION: A BIBLIOMETRIC ANALYSIS OF ‘FOOD PORN’ FROM CULINARY IDENTITY TO DIGITAL PHENOMENON - Boro, Sunita; Dixit, Saurabh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The emergence of digital media has led to a notable increase in the phenomenon known as "food porn," which is defined by the visual representation of visually appealing food. With the heading " Exploring the Evolution: A Bibliometric Analysis of ‘Food Porn’ from Culinary Identity to Digital Phenomenon," this bibliometric study attempts to investigate the development and patterns in academic research on this fascinating topic. Using information from top scholarly databases, researchers conducted a thorough examination of publishing trends, prominent writers, significant organizations, and thematic advancements in "food porn" studies. The study results show a substantial increase in publications over the last ten years, emphasizing the field's multidisciplinary character with contributions from the domains of digital media, cuisine, and cultural studies. The study highlights influential books and writers who have influenced the discourse, and keyword and theme analyses highlight new directions in the field and areas in need of further investigation. This study emphasizes how digital media has a transforming effect on one's culinary identity and provides guidance for future investigations into the cultural and societal ramifications of "food porn."